Competency-based education and training for Community Health Workers: a scoping review - Marium A. Sultan; Emily Miller; Roosa Sofia Tikkanen; Shalini Singh; Arpana Kullu; Giorgio Cometto; Siobhan Fitzpatrick; Onyema Ajuebor; Nicholas Gillon; Anbrasi Edward; Youri P. Moleman; Shivani Pandya; et al. (BMC Health Services Research)
Abstract Background Community Health Workers (CHWs) play a critical role in supporting the delivery of health services globally. Competency-based learning programs can improve the transfer of learning to practice. This scoping review aims to characterize the published literature on competency-based education as an instructional and curricular strategy in community health worker training programs. We conducted a scoping review of the literature to identify how, by who, and in what ways CHWs are trained using competency-based education; and to characterize the extent of available evidence, as well as the gaps in that evidence. Methods We conducted a review of the peer-reviewed literature on CHW competency-based education and training published between January 2010 to March 2023, drawing from four databases: EMBASE, OVID Medline, Web of Science, and CINAHL. We followed the PRISMA guidelines for scoping reviews. A total of 713 articles were reviewed and 236 were included for extraction based on the inclusion and exclusion criteria. Due to methodological heterogeneity, results were analyzed and synthesized only through a descriptive approach. Results The literature on competency-based CHW education and training is most voluminous in high income contexts, primarily the USA. Overall, the included studies described very small-scale training interventions. Study types included observational (qualitative, quantitative, mixed methods, case studies) intervention or experimental studies, systematic or scoping reviews, and literature reviews. The most common practice area included was ‘promotive and preventive services’, whereas ‘personal safety’ was the rarest. Learning programs tailored to CHWs with low-literacy, content tailored to local cultural contexts, and curricula that were co-designed with CHWs were identified in the literature as effective strategies for converting learning to practice. Information on institutional support for CHWs was not provided in most of the articles reviewed. While the focus of our review was on education and training and not broader supports for CHWs, we still found it notable that training was usually discussed in isolation from other related supportive factors, including professionalization and career progression. Conclusions We found considerable academic interest in utilizing competency-based education to support CHWs and improve their work, yet this exploration was largely limited to smaller, ad hoc programs, in high income settings. Learning programs should be tailored to the realities and practice requirements of CHWs. Further work should illuminate the extent to which the design and delivery of education and training activities lead to acquiring and maintaining the requisite competencies.